Մեծ ճաշկերոյթի եւ Հարսանեաց խնջոյքի առակների խորհրդաբանութիւնը եւ դրանց հայ միջնադարեան մեկնութիւնները (Ղուկ. ԺԴ. 16—24, Մատթ. ԻԲ. 1—14) - Բեյլերեան, Յովհաննէս (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Представленные две новозаветные притчи имеют значительные сходства, а также определенные различия, и уже в ранней толковательной литературе они рассматривались не как два варианта одной и той же притчи, а как две схожие, но разные притчи. В статье кратко говорится как об их символической роли в христианском учении, так и об эпизодах восприятия и разъяснения их символики в средневековых армянских толкованиях. Скорее всего, благодаря эсхатологическим значениям этих двух притч, они были включены в богослужебные чтения Армянской Церковью во время литургии Великого поста. These two parables of the New Testament share notable similarities as well as distinct differences, and even in early exegetic literature, they were not regarded as two versions of the same parable, but rather two similar yet distinct parables. The article provides an overview of both the symbolic significance of these parables in Christian teachings and the instances of their perception and explanation of symbolism in medieval Armenian exegesis. Most likely, due to the eschatological implications of these two parables, they were incorporated into the liturgical readings of the Armenian Church during the Great Lent.
Keywords: Կրօնագիտութիւն